SAE Technical Paper Series 2020
DOI: 10.4271/2020-01-0309
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Visualization of Natural Luminosity and Chemiluminescence of Dual Fuel Combustion in an Optically Accessible Engine

Abstract: The engine fueled with methane/diesel is a promising and highly attractive operation mode due to its high performance-to-cost ratio and clean-burning qualities. However, the combustion process and chemical reactions in dual fuel combustion are highly complex, involving short transient pilot-fuel injection into the premixed gaseous fuel charge, autoignition, and combustion mode transition into premixed flame propagation. The motivation of the current investigation is to gain an insight into the combustion dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…9 (bottom). CH 2 O*, CH*, C 2 *, and CO 2 * chemiluminescence have been reported as HRR indicators [29][30][31] , location of the reaction zone 32,33 , an indicator of the equivalence ratio (ER) of the reacting mixture 34,35 . As observed in the reconstructed chemiluminescence emissions, it can be summarized that (1) CH 2 O* as a low-temperature HRR indicator only shows a reliable value at the beginning of the combustion with relatively low intensity.…”
Section: Resultsmentioning
confidence: 99%
“…9 (bottom). CH 2 O*, CH*, C 2 *, and CO 2 * chemiluminescence have been reported as HRR indicators [29][30][31] , location of the reaction zone 32,33 , an indicator of the equivalence ratio (ER) of the reacting mixture 34,35 . As observed in the reconstructed chemiluminescence emissions, it can be summarized that (1) CH 2 O* as a low-temperature HRR indicator only shows a reliable value at the beginning of the combustion with relatively low intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Categorized by their experimental apparatus, they can be divided into Constant Volume Chamber (CVC), 24 Rapid Compression Expansion Machine (RCEM), [25][26][27][28][29][30] single-/multi-cylinder optical engines. 25,[31][32][33][34][35][36][37][38][39][40][41] Dronniou et al 31 observed ignition occurred first in the near-wall region in the piston bowl, burning inwards. They identified the equivalence ratio of the premixed fuel to shape the heat release profile significantly.…”
Section: Pilot-ignited Lean-premixed Natural Gas Enginesmentioning
confidence: 99%
“…Categorized by their experimental apparatus, they can be divided into Constant Volume Chamber (CVC), 24 Rapid Compression Expansion Machine (RCEM), 2530 single- /multi-cylinder optical engines . 25,31–41…”
Section: Introductionmentioning
confidence: 99%
“…To provide a direct validation, simultaneous visualization of the NFL and chemiluminescence, including broadband natural flame image (from 400-700 nm), CH2O* (400 nm), and CH* (430 nm) is performed based on a high-speed color camera (Photron SA-Z) and a bandpass filtered high-speed monochrome camera (Image Doubler + Bandpass filters + Phamton V2012) are captured for validation. More details of the experiments and results can be seen in our previous study [28].…”
Section: Fig 6 Comparison Of the Reconstructed Rgb Image And Raw Imagementioning
confidence: 99%